Education and health examination for the elderly - Yoga Tri Wijayanti; Trimaya Cahya Mulat; M. Khalid Fredy Saputra; Zaenal Zaenal (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
The elderly are one of the population groups that are vulnerable to various health problems. Proper education and health screenings can improve quality of life and prevent diseases that often occur in old age. This service activity aims to identify effective educational approaches and types of health checks that are important for the elderly. Service activities are carried out in the form of free examinations and health counseling to provide information and education about health for the elderly. For counseling activities using the lecture method and focus group discussion. Results show that an integrated educational approach, including information on healthy lifestyles, chronic disease management, and the importance of active socialisation, has a positive impact on elderly health knowledge and behaviours. risk of complications. It can be concluded that education and medical examination are two important aspects of caring for the elderly. An integrated, holistic educational approach can improve the elderly's health knowledge and behaviours, while regular health checkups can help detect health problems early and reduce the risk of complications.